Clinical trials in multiple sclerosis: milestones. (5th July 2018) - Zhang, Yinan; Salter, Amber; Cutter, Gary; Stüve, Olaf
The achievements in multiple sclerosis (MS) therapeutics are founded on the outcomes of clinical trials that demonstrate quantifiable results in treating a disease with an unpredictable course. Much has changed since the early trials in MS from the mid-20th century that compared a potential therapeutic agent with a placebo and measured outcomes based on patients' subjective reports. Advancements over the past decades have simplified diagnosis of the disease and allowed for more quantitative monitoring of its progression alongside support from paraclinical studies. Further collaborative efforts have led to pivotal meetings that steered the direction of future trials and the creation of patient databases that provided important epidemiologic information on trial subjects. These innovations and changes have improved MS clinical trials but challenge future trials to create more efficient designs lest the pace of progress necessarily slows because of the increased time to conduct such studies. As treatment options for MS broaden, clinical trials will continue to incorporate new strategies to identify novel therapies and pathways of intervention.